Pleiotropy of a Stickler syndrome genotype. Issue 6 (November 2022) - Baiyasi, Ahmad; Barbosa, Joshua; Parendo, Anthony; Lin, Xihui
Purpose: To report a case of pleiotropy in the COL2A1 gene typically associated with Stickler Syndrome Type 1. Observations: A patient with a confirmed mutation of the COL2A1 gene presented with an isolated retinitis pigmentosa phenotype. Conclusions: The mutated COL2A1 gene in Stickler Syndrome Type 1 represents a site of pleiotropy, highlighting a change in phenotype across the same genotype potentially due to tissue alternative splicing.